Do Invasive Species have the Medicinal Potential ? - Pradhan, D. K. Kumar (Indian Forester, 2022)
The reported twenty two invasive species representing Asteraceae (9 plant specimens), Malvaceae (2 plant specimens), Euphorbiaceae (2 plant specimens), Solanaceae (2 plant specimens) and one species each in Verbenaceee, Rosaceae, Urticaceae, Cyperaceae, Caryophyllaceae, Polygonaceae and Oxalidaceae are studied in order to understand the medicinal uses. The information obtained from the survey revealed that these invasive species were in use for different purposes such as Lantana camara L. (Family-Verbinaceae) used as anti-pest, Crassocephalum crepidioides (Benth.) S. Moore and Sonchus oleraceus L. for controlling blood sugar and Drymaria cordata (L.) Willdenow ex Schultes and Oxalis corniculata L. for controlling anti-tumurous growth. Interestingly, the trend of hill people found using Rumex nepalensis Spreng. and Pilea microphylla (L.) Liebmann, for settling the dislocated bones, likewise, another plant specimen, Ageratina adenophora (Sprengel) King and Robinson reported treating neurological disorder. Thus, the paper deals the medicinal potentials of the plant specimens whether the invasive specimens possess the commercial viability.